Perhitungan Laba Rugi Model Bagi Hasil Usaha Peternakan Sapi pada Bumdes Banna Lhokseumawe - Dasmi Husin; Hilmi; Azhar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity was carried out at Bumdes (village community owned company) of Banna in Paya Punteut Village, Muara Dua District - Lhokseumawe, Aceh. This village-owned company is known to be engaged in cattle fattening. The motivation and enthusiasm to develop from the management of BUMDes Banna is very high, but the managerial ability of Bumdes management is still very limited. Bumdes, who were expected to grow forward, turned out to be suffering from many problems. One of the problems is when the profit sharing is not proportional. The operating costs incurred are not appropriate. Livestock care work is given to a group of people on the condition that Bumdes bears all operational costs. Profit sharing is based on the revenue sharing system where Bumdes gets a 40% portion of the sales of cows. The service method used in the dedication of the application of science and technology is a participatory method, namely by making continuous observations, speeches, and direct demonstration (demonstration) methods. This activity is capacity building assistance for six months. The focus is on strengthening productivity and management such as compiling financial reports, business visibility, and strengthening archives management. The results of community service activities indicate that the profit sharing system has not fully met the standard accounting standard format, especially in the preparation of the income statement. In order for Bumdes to no longer feel that it is making a profit, but in fact it is a loss, the formulation of the AD-ART (regulation of company village) needs to be revised with the approval of Bumdes stakeholders through village meetings. Furthermore, the preparation of financial statements must be based on applicable accounting standards.